Experimental Investigation of Average Nusselt Number Variations in a Heat Pipe-Evacuated Tube Solar Collector due to Presence of Acetone-Graphene Nanofluid - S. Y. Afshoon; R. Shafaghat; M. Gorji Bandpy (Iranica Journal of Energy and Environment)
This study investigates the enhancement of thermal performance in Evacuated Tube Solar Collectors (ETCs) by integrating graphene nanoparticles into the heat transfer fluid. Improvement the efficiency of ETCs is crucial for maximizing solar energy utilization, particularly in regions with diverse climatic conditions. To achieve this, we conducted experiments comparing the thermal performance of the ETC under two conditions: with and without graphene nanoparticles, and at varying flow rates of condenser water (5, 10, 15, and 20 L/h) in an open space in Babol, northern Iran, over two periods in August 2022. Measurements included ambient temperature, input and output water temperatures, heat pipe temperature, and water flow rate. Key performance indicators, such as the average Nusselt number, useful heat output, and convection heat transfer, were calculated. The results indicate that the Nusselt number increased by 10.64% and overall thermal performance improved when utilizing the acetone-graphene nanofluid at a flow rate of 20 L/h under vacuum conditions (-0.6 bar) with a volume fraction of 0.08% nanoparticles. This work demonstrates a significant enhancement in thermal energy storage capabilities of ETCs, showcasing the potential of nanofluids in solar thermal applications, thereby contributing novel insights into the engineering optimization of solar collectors.